The 'M' in SMEC: A short history of the mathematics education presence - Malone, John (2011)
In this paper I examine the history of the integration of mathematics education into the Science Education Centre, which had been established by physicist, John de Laeter, within the School of Science and Engineering at Curtin University in Perth, Australia. De Laeter's vision for science education was that teachers should have access to professional education that allowed them to extend their discipline and pedagogical knowledge using strategies that brought together theory and practice in ways that were meaningful for teachers. This model was expanded when mathematics education was also included, paving the way also for technology education. I present the history of this integration laying out the themes that are important for the continued educational effectiveness of the Science and Mathematics Education Centre (SMEC) and the role that mathematics education has played in this process. As the title suggests, this article focuses on the activities of the group of mathematics educators who have worked within the Science and Mathematics Education Centre of Curtin University since it was established 30 or so years ago and who have contributed to its reputation. The two streams operated then and now more-or-less independently in matters of student thesis topic choice but offered students opportunities for interaction that might not have been available if the "M" had not been incorporated into the Science Education Centre (SEC). This article's focus is on the mathematics educators who contributed to the Centre's success and reputation, highlighting the synergistic relationship between mathematics and science that helped to make SMEC a leading center for mathematics and science education. © 2011 Springer Science+Business Media B.V.